2022
DOI: 10.1002/anie.202206706
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Energy and Solvent‐Dependent Chirality Transfer within a BINOL‐Perylene Hetero‐Cyclophane

Abstract: Multichromophoric macrocycles and cyclophanes are important supramolecular architectures for the elucidation of interchromophoric interactions originating from precise spatial organization. Herein, by combining an axially chiral binaphthol bisimide (BBI) and a bay-substituted conformationally labile twisted perylene bisimide (PBI) within a cyclophane of welldefined geometry, we report a chiral PBI hetero-cyclophane (BBI-PBI) that shows intramolecular energy and solvent-regulated chirality transfer from the BBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 41 publications
0
23
0
1
Order By: Relevance
“…14 Due to their accessibility and relatively high rotational barriers, some BINOL derivatives with extended conjugation have been prepared 15 and the enantiomeric BINOL derivatives, which also served as chiral inducers or transfer scaffolds, were introduced into the hydrocarbons to create diverse chiral materials. 16–18 For instance, by the introduction of chiral binaphthyl scaffolds, different chiral carbon nanorings or macrocycles were prepared as circularly polarized luminescence (CPL) emitters. 16 Quite recently, Würthner et al reported a helical perylene bisimide (PBI) by combining an axially chiral binaphthol bisimide (BBI), in which the BBI serves as a chirality transfer unit to generate helical twisted PBI.…”
Section: Introductionmentioning
confidence: 99%
“…14 Due to their accessibility and relatively high rotational barriers, some BINOL derivatives with extended conjugation have been prepared 15 and the enantiomeric BINOL derivatives, which also served as chiral inducers or transfer scaffolds, were introduced into the hydrocarbons to create diverse chiral materials. 16–18 For instance, by the introduction of chiral binaphthyl scaffolds, different chiral carbon nanorings or macrocycles were prepared as circularly polarized luminescence (CPL) emitters. 16 Quite recently, Würthner et al reported a helical perylene bisimide (PBI) by combining an axially chiral binaphthol bisimide (BBI), in which the BBI serves as a chirality transfer unit to generate helical twisted PBI.…”
Section: Introductionmentioning
confidence: 99%
“…Chemicals and solvents were purchased from commercial suppliers and used without further purification. Precursor 2 46 , [5]helicene 52 and N - Boc -4-(aminomethyl)benzylamine 53 were synthesized according to literature known procedures (see Supplementary Information ). The separation of the enantiomers of [5]helicene was achieved by chiral HPLC (DCM/ n -hexane 3:7, flow rate 6.5 mL/min) with enantiomeric excess of >95%.…”
Section: Methodsmentioning
confidence: 99%
“…Among the preparation strategies, energy transfer has proved to be a powerful approach for constituting CPL materials. Fluorescence resonance energy transfer (FRET) has been broadly adopted to realize and adjust CPL emission. , More recently, circularly polarized fluorescence resonance energy transfer (C-FRET) has become a relatively emerging methodology for achieving CPL. Nonetheless, both the variety and number of such studies are still highly limited. According to the features of an energy donor and energy acceptor, the approaches for realizing CPL via energy transfer can be generally grouped into two categories: intermolecular FRET and intramolecular FRET. , The elegant studies have clearly confirmed the huge potential of C-FRET toward developing CPL materials. However, nearly all of the reported studies using C-FRET for CPL integrate two processes, i.e., energy transfer and chirality transfer in one single system.…”
Section: Introductionmentioning
confidence: 99%